Web Application Hacking with Burp Suite - Cosentino, Scott (Packt Publishing, 2021)
Learn essential techniques with Burp Suite to detect vulnerabilities that cause web applications to be compromised About This Video Learn how to find and exploit common vulnerabilities with Burp Learn how Burp Suite can help automate attacks Learn using hands-on examples In Detail Burp Suite contains an array of penetration testing and vulnerability finder tools. It is mainly used to identify the vulnerabilities of web applications. In this course, you will learn essential techniques with Burp Suite to detect vulnerabilities that cause web applications to be compromised. The course starts off with demonstrating how to set up your project in Burp Suite. It also introduces the different modules included in the Burp Suite. You'll learn to identify information disclosure vulnerability and expose sites leaking sensitive information. You'll also learn about insecure decentralization vulnerability and how this can be exposed. Web applications use WebSocket to communicate with the user. Testing web sockets for vulnerabilities is also covered in this course. You'll also learn how to simulate the directory traversal attack and read files that are running. Finally, you will learn about some other attacks such as the external entity injection (XXE), cross-site scripting (XSS), and SQL injections. With this, you will have all the skills in your arsenal to test web applications.